2019
DOI: 10.3389/fimmu.2019.01972
|View full text |Cite
|
Sign up to set email alerts
|

IL-23/IL-17 Axis Activates IL-1β-Associated Inflammasome in Macrophages and Generates an Auto-Inflammatory Response in a Subgroup of Patients With Bullous Pemphigoid

Abstract: Bullous Pemphigoid (BP) is a skin autoimmune blistering disease characterized by immune-mediated degradation of the dermo-epidermal junction and release of a large number of inflammatory cytokines. Interleukin-1β (IL-1β) is a pleiotropic pro-inflammatory cytokine associated with inflammasome activation and known to be pivotal in several auto-immune and auto-inflammatory diseases. We sought to clarify the presence of inflammasome-dependent IL-1β and to investigate its role in BP. Skin biopsy specimens ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 31 publications
0
24
1
Order By: Relevance
“…As previous reports have suggested, IL‐17 plays pivotal roles in the development of BP by targeting myeloid cells, such as macrophages 4,12,18,19 . Indeed, Le Jan et al 4 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…As previous reports have suggested, IL‐17 plays pivotal roles in the development of BP by targeting myeloid cells, such as macrophages 4,12,18,19 . Indeed, Le Jan et al 4 .…”
Section: Discussionmentioning
confidence: 90%
“…As previous reports have suggested, IL‐17 plays pivotal roles in the development of BP by targeting myeloid cells, such as macrophages 4,12,18,19 . Indeed, Le Jan et al 4 . reported that the IL‐23/IL‐17 axis activates inflammasomes in macrophages, leading to the release of IL‐1β, which induces autocrine stimulation of macrophages to produce MMP9 in BP patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, Le Jan et al [93] identified IL-17 and related cytokines such as IL-22 and IL-23 in the serum and blister fluids of BP patients; these cytokines may lead to a feedback loop and the perpetuation of the autoinflammatory process increasing MMP-9 secretion and CXCL10 expression from leukocyte cells [94]. In line with this, sustained or enhanced serum levels of IL-17 were associated with relapses in BP [93]. Therefore, the marked association between OP and pemphigus can be explained at the molecular level by the immunopathogenic process and by the pro-inflammatory cells and cytokines shared in both disorders that lead to a net increase in bone resorption [92].…”
Section: Blistering Diseasementioning
confidence: 99%
“…Pemphigus is an autoimmune disease dependent on T cells principally of self-reactive Th2 cells, which also involves pro-inflammatory cytokines of the innate immune system, such as TNF, IL-1, and IL-6 [92]. Moreover, Le Jan et al [93] identified IL-17 and related cytokines such as IL-22 and IL-23 in the serum and blister fluids of BP patients; these cytokines may lead to a feedback loop and the perpetuation of the autoinflammatory process increasing MMP-9 secretion and CXCL10 expression from leukocyte cells [94]. In line with this, sustained or enhanced serum levels of IL-17 were associated with relapses in BP [93].…”
Section: Blistering Diseasementioning
confidence: 99%